From Biomedical Applications of Alginate towards CVD Implications Linked to COVID-19 - Angela Spoială; Cornelia-Ioana Ilie; Denisa Ficai; Anton Ficai; Ecaterina Andronescu (MDPI AG, 2022)
In the past year, researchers have focused their attention on developing new strategies for understanding how the coronavirus affects human health and developing novel biomaterials to help patients with cardiovascular disease, which greatly increases the risk of complications from the virus. Natural biopolymers have been investigated, and it has been proven that alginate-based materials have important features. This review presents an overview of alginate-based materials used for developing innovative biomaterial platforms for biomedical applications to mitigate the effects of the coronavirus. As presented in this review, COVID-19 affects the cardiovascular system, not only the lungs. The first part of the review presents an introduction to cardiovascular diseases and describes how they have become an important problem worldwide. In the second part of the review, the origin and unique properties of the alginate biopolymer are presented. Among the properties of alginate, the most important are its biocompatibility, biodegradability, low cost, nontoxicity, unique structure, and interesting features after chemical modification. The third section of the review illustrates some of the functions of alginate in biomedical, pharmaceutical, and drug delivery applications. Researchers are using alginate to develop new devices and materials for repairing heart tissues that have been damaged by the coronavirus. Further, insights regarding how cardiovascular disease affects COVID-19 patients are also discussed. Finally, we conclude the review by presenting a summary of the impacts of COVID-19 on cardiovascular patients, their implications, and several hypothetical alginate-based treatments for infected patients.